Implications of Metabolically Healthy Obesity—Ganesha Speaks - Shaikh, Rukia Surya; Patil, Pratiksha; Lathia, Tejal (Journal of Social Health and Diabetes, 2019)
The cherubic elephant God Ganesha, a favorite of millions of Hindu devotees, sports a round belly. Humans who have a round belly would be classified as obese. Is all obesity unhealthy? What is metabolically healthy obesity? Different definitions and criteria make the discussion of metabolically healthy obesity difficult and challenging.
Keywords: obesity; metabolic; diabetes; hypertension; cardiovascular disease